What is next in Asian Catch-up – A Technological View - Trang, Do Huyen (VNU Journal of Science: Policy and Management Studies; Vol 38 No 2DO - 10.25073/2588-1116/vnupam.4402, 2022)
The world has witnessed the rise of less developed economies in catching up with or, sometimes, over taking industrialised countries. This has shown in narrowing the gap in growth and development indicators such as productivity, national income, market share and technological capability. They can be countries that were defeated in wars like Germany, Japan, or even the United States during 1950s, or it can be countries that historically and politically less developed in terms of industrialisation like South Korea (hereinafter Korea), Singapore, Taiwan, etc. or lately China, India, Brazil. After the first and the second wave of the successful catch-up, questions have been posed on who among the lagging behind can possibly move to more advanced position in the technolgoical development ladder.